A teoria da prova no direito tributário: uma análise dos Standards de prova exigíveis no lançamento, arbitramento e imputação de infrações, conforme o Código Tributário Nacional - Pereira, Ricardo Oliveira (2024)
This dissertation aims to investigate the probative standards required in the context of Brazilian Tax Law. Probative standards are the sufficiency criteria required by law for a factual hypothesis to be considered proven. The research methodology, of a juridical-dogmatic nature, is divided into two parts. In the first, epistemic criteria for the formulation of the standards are established. In the second, criteria that underpin the degree of probative sufficiency in Tax Law are indicated, specifying in which situation each standard is applicable and how it is applied. Finally, three probative standards applicable to Tax Law are presented. The ordinary standard, which uses criteria associated with clear and convincing evidence, is applicable to tax assessments in general, based on article 142 of the National Tax Code. The reduced standard, associated with the preponderance of evidence, is applicable in cases of arbitration, based on article 148 of the CTN. The qualified standard, which adopts the criteria of proof beyond a reasonable doubt, is required in cases of infraction imputation, as provided by article 112 of the CTN